Pemberdayaan Masyarakat Petani Berbasis Partisipasi (Studi Kasus Pemanfaatan Burung Hantu Tyto Alba Sebagai Pemangsa Hama di Desa Tlogoweru Kecamatan Guntur Kabupaten Demak) - Von Dasa, Stephanus Piter; Taufiq, Ahmad; Adhi, Suwanto (Journal of Politic and Government Studies, 2017)
ABSTRACTAbstract. Empowering communities is an attempt to enhance the dignity of the community who are unable to escape from the trap of poverty and underdevelopment. The success of the community building definable as well from the community participation and the role of government related. Tyto Alba Program in Tlogoweru Village is one of the government’s efforts in Tlogoweru Village of empowering communities who have not been able to overcome the problem of crop failures due to a very tough mouse pest control.The research method used is the qualitative approach and the techniques of data collection through interviews and documents. Informants in this research are The Head of Tlogoweru Village, Tlogoweru Village Secretary, Chairman of The Tyto Alba Developer Team, and the community of Tlogoweru Village.The research results showed that community empowerment of farmers in Tlogoweru Village through Tyto Alba Program has successfully overcome the crop failures as well as making community could develop other business. Empowerment implemented through Empowerment of Human Development, Empowerment of Institutional Development, Empowerment of Business, and Empowerment of Environment.The recommendations could be made to The Government of Tlogoweru Village was able to manage The Quarantine Place Of Tyto Alba better as well as the development of physical infrastructure to support Tlogoweru Tourist Village.Keywords: Empowerment, Agriculture, Tyto Alba.